Persistent effects on bovine granulosa cell transcriptome after resolution of uterine disease. Issue 1 (July 2019) - Piersanti, Rachel L; Horlock, Anthony D; Block, Jeremy; Santos, José E P; Sheldon, I Martin; Bromfield, John J
Abstract : Metritis is associated with reduced fertility in dairy cows, but the mechanisms are unclear because the disease resolves several weeks before insemination. One hypothesis is that metritis causes persistent changes in granulosa cells during follicle development, which might be evident in the transcriptome of granulosa cells from dominant follicles weeks after parturition. To test this hypothesis, we collected the follicular fluid and granulosa cells from dominant follicles 63 days post partum from cows previously diagnosed with metritis, at least 6 weeks after resolution of the disease and from cows not diagnosed with metritis (control cows). Bacterial lipopolysaccharide was detected in follicular fluid, and concentrations were associated with follicular fluid IL-8 and glucose concentrations. Transcriptome analysis using RNAseq revealed 177 differentially expressed genes in granulosa cells collected from cows that had metritis compared with control cows. The most upregulated genes were ITLN1, NCF2, CLRN3, FSIP2 and ANKRD17, and the most downregulated genes were ACSM1, NR4A2, GHITM, CBARP and NR1I3 . Pathway analysis indicated that the differentially expressed genes were involved with immune function, cell–cell communication, cell cycle and cellular metabolism. Predicted upstream regulators of the differentially expressed genes included NFκB, IL-21 and lipopolysaccharide, which are associated with infection and immunity. Our data provide evidence for a persistent effect of metritis on the transcriptome of granulosa cells in ovarian follicles after the resolution of disease.